When the lion feeds - Smith, Wilbur A. (Smith, Wilbur A. Courtney series., 2006)
WHEN THE LIONS FEEDS is the story of South Africa at the burgeoning time of the gold rush in the 1890s. Sean Courtney was raised in cattle country, accidently maimed his twin brother Garry as a boy. In inflicting weakness, Sean came to despise weakness in all. This, plus his own strength, was to dictate Sean's iron resolve to win, no matter how much the gamble cost. After a stint fighting the Zulu tribes, Sean trys his luck in the gold fields. Venturing an impossible claim which miraculously proves out, Sean gains wealth beyond counting and power. Power that was unmanageable without cunning. But cunning was an art he was to learn the hard way.